Acceptance of Using Thai Air Asia’s Online Application of Thai Senior Citizens - Witthawassamrankul, Krit; Nutchirathorn Nualsom; Weerapong Nanthasing (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
This research mainly aimed to 1) study the acceptance of Thai Air Asia Airline’s Application and 2) to study the variables affecting the senior citizens’ acceptance of the airline. The research instrument was the questionnaires which were distributed to 400 Thai senior citizens. The statistics were frequency, percentage, mean, standard deviation, t-test, One-Way ANOVA at a statistical significance level of 0.05. The results found that mostly respondents were females, ages between 60-74, having lower than bachelor degree level, the current or previous occupation before retirement was freelancers, staying and learning from their children, frequency of use was 1-2 times per year, and objective of flying was travelling. The results of overall acceptance of Thai Air Asia’s online application was at a high level (mean = 3.70, S.D.= 0.909). The hypothesis testing found that the different education level, occupation, learning, frequency of use and objectives of travelling, not genders and age ranges affected the acceptance level. The results showed that learning and social factor, particularly staying with their children and learning from the children were the factors affecting the senior citizens’ acceptance level of Thai Air Asia Airline’s application.